Biocontrol efficacy of endophytic bacteria from Mimosa pudica L. against Fusarium oxysporum in kepok banana (Musa acuminata × balbisiana) in vitro - Ismiah, Alvi; Saylendra, Andree; Isminingsih, Sulastri; Roidelindho, Kiki (Universitas Lancang Kuning, 2025)
Fusarium oxysporum f. sp. cubense (Foc) is a major fungal pathogen responsible for Fusarium wilt disease in banana plants, significantly reducing productivity and leading to substantial economic losses. This study aimed to evaluate the biocontrol potential of endophytic bacteria isolated from Mimosa pudica L. against Foc through an in vitro assay. A completely randomized design (CRD) with four treatments was employed, including a negative control (CP0), a positive control (CPF0), and two endophytic bacterial isolates from Mimosa pudica L. (BEP8 and BEP15), each with four replications. The antagonistic activity of these isolates was assessed using the dual culture method. The results demonstrated that BEP8 and BEP15 significantly inhibited Foc growth from 1 to 5 days after inoculation (DAI), with maximum inhibition rates observed on day 4, reaching 36.60% and 37.52%, respectively. These findings suggest that endophytic bacteria from Mimosa pudica possess potential as biocontrol agents against Foc. However, further molecular identification and greenhouse trials are necessary to confirm their efficacy in real-world applications.